A managerial perspective of the role of secondary school learners in the development and implementation of a code of conduct. - Steinmann, C.F. (My University, 2013)
This study investigated the rights of learners on the Representative Council of Learners (RCL) in secondary schools to develop and implement a code of conduct for learners through their participation on the school governing body (SGB). The study attempted to determine how active involvement of learners on the SGB is perceived by both the RCL and School Management Teams (SMTs). The problem was investigated by means of a literature review and qualitative inquiry. Individual interviews were held with RCL members and chairpersons, school principals and a chairperson of one SGB in three secondary schools in Tshwane, South Africa. Findings indicated barriers to the roles of learners in developing and implementing a code of conduct.
Keywords: Code of conduct, secondary schools, school management.